Crohn's Disease with Orofacial Granulomatosis Is a Distinct Disease Subtype, or Is It?. Issue 7 (July 2016) - Hoekman, Daniël R.; Diederen, Kay; Benninga, Marc A.
Abstract : Article first published online 7 June 2016.